Guidelines for the Evaluation and Management of Status Epilepticus - Brophy, Gretchen M.; Bell, Rodney; Claassen, Jan; Alldredge, Brian; Bleck, Thomas P.; Glauser, Tracy; LaRoche, Suzette M.; Riviello, James J.; Shutter, Lori; Sperling, Michael R.; Treiman, David M.; Vespa, Paul M. (Neurocritical care, 2012)
Status epilepticus (SE) treatment strategies vary substantially from one institution to another due to the lack of data to support one treatment over another. To provide guidance for the acute treatment of SE in critically ill patients, the Neurocritical Care Society organized a writing committee to evaluate the literature and develop an evidence-based and expert consensus practice guideline. Literature searches were conducted using PubMed and studies meeting the criteria established by the writing committee were evaluated. Recommendations were developed based on the literature using standardized assessment methods from the American Heart Association and Grading of Recommendations Assessment, Development, and Evaluation systems, as well as expert opinion when sufficient data were lacking.